Integration Of Local Wisdom Values In History Learning As An Effort To Strengthen Character Education - Astrini Eka Putri (Sean Institute, 2024)
Character education is an important element in Indonesia's national education system, aiming to form a young generation who are intelligent and have noble morals. History learning has great potential in shaping student character through the integration of local wisdom values. This research explores how the values of West Kalimantan's local wisdom, such as gotong royong, harmony with nature, tolerance, respect for customs, and local wisdom in resource management, can be internalized in history learning to strengthen character education. The implementation of these values requires a systematic and creative approach from the teacher, using active and participatory learning methods as well as diverse media and learning resources. Methods such as documentaries, field trips, and digital technologies can be used to enrich students' understanding. Continuous evaluation and development are needed to ensure the successful integration of local wisdom values in the educational curriculum. This study emphasizes the importance of the role of teachers in using various strategies to internalize the values of local wisdom in history learning, to strengthen student character education. The provided bibliography provides relevant references to the topic, supporting further research and practical implementation in the field.